2015
DOI: 10.3906/zoo-1307-35
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate communities along the Velika Morava River

Abstract: This paper presents the results of a faunistic study of the macrozoobenthos of the Velika Morava River. The investigation was conducted during the summer and autumn months in 2010. A total of 84 macroinvertebrate taxa have been identified, with Insecta (Ephemeroptera) as the most diverse and Oligochaeta as the most abundant groups. A tubificid worm, Limnodrilus hoffmeisteri, was the most important species with regard to relative abundance and frequency of occurrence. Two rare and endangered species, Theodoxus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It was demonstrated that stoneflies were no longer present in the polluted site, where they once were, because the pollutant stream dissolved oxygen content had decreased. Tubifex were more abundant in polluted site, which was the indicator of sewage pollution; their abundance was high in another study in autumn, due to the absence of rainfall and low natural filtration at polluted site (Markovic et al, 2015). The productive areas for macro-invertebrates are riffles, leaf packs, soft sediments and root/bank habitat.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that stoneflies were no longer present in the polluted site, where they once were, because the pollutant stream dissolved oxygen content had decreased. Tubifex were more abundant in polluted site, which was the indicator of sewage pollution; their abundance was high in another study in autumn, due to the absence of rainfall and low natural filtration at polluted site (Markovic et al, 2015). The productive areas for macro-invertebrates are riffles, leaf packs, soft sediments and root/bank habitat.…”
Section: Resultsmentioning
confidence: 99%
“…Besides sensitivity to pollution, interactions with invasive species could influence this species. A large predatory amphipod Dikerogammarus villosus (Sowinsky, 1894) nowadays is one of dominant gammarids in the largest Serbian waterway -the Danube River (Paunović et al, 2007;Borza et al, 2015), and present in other larger rivers such as the Tisa (Zorić et al, 2015) and the lower parts of the Sava (Paunović et al, 2012) and the Velika Morava (Marković et al, 2015). Kureck et al (2001) found a significant decrease of the E. virgo in presence of D. villosus because of predation (from Haas et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Considering representatives of the genus Corbicula, C. fluminalis was recorded in a small number of localities in low abundance. In contrast, C. fluminea was present in many localities on the Danube [24], as well as on the Sava [21,29], and along the entire course of the Tisa, and Velika Morava [22,23,25,27,53] as a dominant alien species.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed overview of only half of allochthonous species is given up to now: Branchiura sowerbyi [5,6], Corbicula fluminea and C. fluminalis [7], Craspedacusta sowerbii [8], Dreissena rostriformis bugensis [9], Faxonius limosus [10], Hypania invalida [11], Eriocheir sinensis [12,13], Manayunkia caspica [14], Physa acuta [15][16][17] and Sinanodonta woodiana [18]. In addition, allochthonous species of different aquatic systems in Serbia were the subject of several publications, and the most comprehensive research was carried out on the Danube, Sava, Tisa, and Velika Morava rivers [4,[19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%